Impacts of land use change due to biofuel crops on climate regulation services: Five case studies in Malawi, Mozambique and Swaziland. (July 2018) - Romeu-Dalmau, Carla; Gasparatos, Alexandros; von Maltitz, Graham; Graham, Alastair; Almagro-Garcia, Jacob; Wilebore, Beccy; Willis, Katherine J.
Abstract: Understanding changes in carbon sequestration due to land conversion is key for elucidating the true potential of biofuel landscapes to provide climate regulation ecosystem services. In this study, we focus on the two most promoted biofuel crops in southern Africa, Jatropha and sugarcane, to analyse the land use change effects and associated carbon impacts of growing biofuel crops in five study sites in Mozambique, Malawi and Swaziland. We found that, considering a 20-year cycle, carbon stocks in aboveground biomass are higher for sugarcane than for Jatropha. However, as soil organic carbon (SOC) is generally the main carbon pool, total carbon stocks (considering biomass and soil) will highly depend on SOC. Our results show that, in our study sites, sugarcane replaced land uses with low carbon stocks (low-density forest and agriculture), and as a result carbon gains occurred due to land use change. In the Jatropha projects, carbon gains are observed in the smallholder scheme as agricultural land was converted to Jatropha, but carbon debts occurred in the Jatropha plantation as high-density forest was cleared to grow this feedstock. Finally we show that, if a plantation of sugarcane or Jatropha is envisioned to be located in the studied regions, more forested land could potentially be converted into sugarcane (30–44% of forest) than into Jatropha (24–32%), without creating carbon debts due to land conversion. To our knowledge, this is the first comparative study of the carbon impacts of land use change of the main biofuel crops in southern Africa. Highlights: We assess the carbon impacts of land conversion to Jatropha and sugarcane. Aboveground carbon stocks are higher for sugarcane than for Jatropha. Carbon stocks highly depend on soil organic carbon as it is the main carbon pool. In all sugarcane projects carbon gains are observed due to land use change. Carbon debts are observed in the Jatropha plantation due to land conversion.